The Effect of Clean and Healthy Lifestyle Education on Knowledge and Attitudes Regarding Type 2 Diabetes Mellitus Among High School Student - Najwa Annejang; fanny septiani farhan (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Diabetes Mellitus (DM), a chronic metabolic disease characterized by elevated blood glucose levels caused by impaired insulin secretion, insulin resistance, or both. The prevalence of Type 2 Diabetes Mellitus among adolescents has been increasing, mainly due to unhealthy lifestyle patterns. The Clean and Healthy Lifestyle/Prilaku Hidup Bersih dan Sehat (PHBS) is a set of consciously practiced health behaviors aimed at improving and maintaining health, including consuming balanced nutritious foods, engaging in regular physical activity, maintaining personal hygiene, and avoiding smoking. PHBS education is considered essential in preventing Type 2 DM from an early age. This research aims to determine the effect of PHBS education on the prevention of Type 2 DM among adolescents at SMA Daar El-Qolam, Banten. The study is a pre-experimental design using a one-group pre-test and post-test approach. Data were collected using questionnaires assessing knowledge, attitudes, and behaviors related to diet, physical activity, and smoking, and were analyzed using the Wilcoxon test. The results showed a significant improvement in knowledge (p<0.05) as well as positive changes in attitudes and behaviors regarding healthy eating and physical activity after the intervention. The study concludes that PHBS education effectively enhances adolescents’ knowledge, attitudes, and preventive behaviors toward Type 2 DM. School-based health education programs are recommended as promotive and preventive measures to reduce the risk of non-communicable diseases among high school student.